Nutritional counselling and its effects on diet, nutritional knowledge and status, physical activity and quality of life in a Southern Europe population: evaluation of a health promotion programme (Italian Journal of Public Health, 2011)
Background: Health promotion and primary prevention are key points for fighting the increase in non- communicable diseases. Aim: To test the effectiveness of a nutritional counselling programme in improving nutritional behaviours, knowledge and status, physical activity and health-related quality of life in a general population. Methods: In the period between January–December 2007, we studied the application of the nutritional counselling programme (NCP) developed by Local Health Agency 10 (Florence-Italy). We compared , diet, nutritional knowledge, physical activity, health related quality of life (measured by SF36 questionnaire), body mass index (BMI) and waist circumference before and after a two months intensive nutritional counselling programme using the paired t test and McNemar test. Diet, nutritional knowledge, physical activity, socio-demographic and morbidity information were collected through questionnaires. BMI and waist circumference were assessed by a medical doctor. Results: We enrolled 74 persons, 59 of whom completed the educational programme. Of these, 34 had a nutritional status assessment after the programme. Mean age was 49 years, 80% were females. BMI, waist circumference and diet, except for water intake, did not change. The percentage of people who had “never exercised in a week" decreased from 46% to 17% (p
Keywords: nutritional counselling; physical activity; diet; health-related quality of life; southern Europe